Religijność a tożsamość narodowa polskich migrantów w Wielkiej Brytanii w dobie brexitu - Kozak, Jarosław; Fel, Stanisław; Wódka, Marek (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2021)
Religion plays an important role in the life of individuals, societies and entire national communities. It has a particular impact where religious affiliation is an important part of national identity. The aim of this article is to explore the influence of religiosity on the identity attitudes of Poles abroad under conditions of migration. The analysis focuses on assessing the impact of the self-declaration of faith of the Polish post-accession migrants in Great Britain on their national identity. Sociological research was conducted with a questionnaire on a sample of 620 Poles living in the UK. The analysis of quantitative research has shown that despite the decreasing rate of respondents’ self-declaration of faith, religion is still strongly related to their national identification. The influence of the religious factor on the declared national affiliation to the country of origin is most evident among the firm believers, while those respondents who declare a shared national affiliation – declaring a strong sense of belonging to the country of settlement – were characterised by a lower value of the religiousness index.